2-D boundary value problems of thermoelasticity in a multi-wedge - multi-layered region. Part 2. Systems of integral equations - Mishuris, G.S. (Archives of Mechanics, 1997)
In the paper, arbitrary 2-D BVP of termoelasticity in a wedge-shaped - layered region are reduced to special systems of singular integral equations with fixed point singularities. For this purpose, the Fourier and Mellin integral transforms of the solutions in the layered and wedge-shaped parts of the domain are "fitted" together along the common interface. This interface is characterized by the conditions of given discontinuities of displacements and tractions. The theory, developed by the author elsewhere, is applied to investigate the systems obtained. The results, concerning existence and properties of the solutions are presented depending on the exterior boundary conditions. The numerical method applied to solve the systems of equations is justified.